Sociologie des relations professionnelles / Sociologie du travail : les relations professionnelles - Bourque, Reynald (Relations industrielles / Industrial Relations, 2010)
The article reviews the books, "Sociologie des relations professionnelles, " new edition, by Michel Lallemant, and "Sociologie du travail : les relations professionnelles" by Antoine Bevort and Annette Jobert.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z